Desenvolvimento larval de Dardanus insignis (Saussure) (Crustacea, Decapoda, Diogenidae), em laboratório - Hebling, Nilton José [UNESP] (1995)
The developmental stages of Dardanus insignis (Saussure, 1858) from first through eighth zoea and megalopa are described and illuslraled. The experiments were carried out involving 100 larvae, obtained from ovigerous females collected on the north littoral of the state of São Paulo, Brazil. The larvae were kept in individual containers, with water of 34 salinity and fed with freshly hatched nauplii of Artemia; room temperature was maintained at 25±1ºC. The larval characters of this species are compared with Dardanus arrosor (Herbst, 1796). the only species of the genus that has also heen reared in laboratory.